Pengaruh Kompetensi, Disiplin, Lingkungan Kerja Dan Reward Terhadap Kinerja Pegawai Polisi Di Polres Labuhanbatu Selatan - Esther Marisa Sihite; Meisa Fitri Nasution; Fadzil Hanafi Asnora (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this study was to prove the effect of Competence (X1), Discipline (X2), Environment (X3) and Reward (X4) on employee performance (Y) Research location at the South Labuhanbatu police station, The research data used as a population is all police personnel of South Labuhanbatu POLRES, namely 204 people so that researchers use census sampling techniques, namely the entire population is sampled, namely 204 people. the questionnaire was designed using a Likert scale level 1-5. Data analysis using spss. The test results prove that competence has a significant effect on the performance of police employees at the South Labuhanbatu Police Station with an effect of 66%, Work Discipline has an insignificant effect on the performance of police employees at the South Labuhanbatu Police Station with an effect of 6.6%, and the effect of the Work Environment is insignificant on the performance of police employees at the South Labuhanbatu Police Station with an effect of 11%. Reward has a significant effect on the performance of police employees in the south labuhanbatu police station with an effect of 43%.